Rainfall Distribution and the Possibility for Healthy and Fresh Drinking Water - Anna, Alif Noor (Universitas Muhammadiyah Surakarta, 1990)
The information of rain water quality in Indonesia is rarely recorded, where as it is important for the region in which the source of fresh water is unavailable. Rain water composition is mostly ascertained by water vapour and ions which are available in the atmosphere during vapouration. In fact the rain water composition of coast region is sea water like and rain water chemical composition of urban are then become HNO3 and HSO4, while rain water of active vulcanic region eventuality has a high sulphur-wombed so that its quality sulphuric-acid. For the region in which the source of fresh water is unavailable the rain water is previously sterilized. Sterilization is consecutively done by adding salts, killing all bacteria, spores, and filltering.